Works council introductions: Do they reflect workers' voice? - Michael Oberfichtner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2013)
Using a large linked employer-employee dataset from Germany, I investigate workers' decision to introduce a works council as an exit-voice consideration. Thereby, I explore the collective voice face of introductions, while previous studies focus on the monopoly aspect. Controlling for unobserved plant heterogeneity, council introductions are more likely if workers have high plant-specific human capital or earn high wages, whereas no association between the labor market situation and introductions shows up. The findings on human capital and wages are consistent with the idea that workers trade off introducing a council against exit as well as with workers trying to protect an existing distribution of rents. Redoing the analysis for a sample of plants in which it is less relevant for workers to protect themselves against management decisions yields similar results supporting the voice interpretation.
Keywords: J53; 330; co-determination; works councils; works council introductions; workers' voice